Teachers with Physical Disabilities in the Brazilian Educational Scenario - Fabrício de Paula Santos; Marco Antônio Melo Franco (Revista Diálogo Educacional)
This systematic review aimed to elucidate how research has addressed the reality of teachers with physical disabilities in Brazil, considering studies published from 2011 to 2021. The systematic review was conducted in accordance with the guidelines described in the PRISMA statement. It included qualitative studies available in the Brazilian Digital Library of Theses and Dissertations (BDTD) and SciELO databases focused on the educational and professional trajectories of these teachers. Only two studies of the 697 records identified met the inclusion criteria. The analysis revealed that in addition to physical barriers, teachers face social stigmas which impact the perception of their pedagogical skills, highlighting the influence of body image and ableism in their daily professional lives. The conclusion is that structural prejudice and the scarcity of inclusive policies perpetuate challenges, while the literature still shows significant gaps in the teaching experiences of this population.